Use of probiotics in aquaculture of China—a review of the past decade. Issue 86 (March 2019) - Wang, Anran; Ran, Chao; Wang, Yanbo; Zhang, Zhen; Ding, Qianwen; Yang, Yalin; Olsen, Rolf Erik; Ringø, Einar; Bindelle, Jérôme; Zhou, Zhigang
Abstract: China is the largest aquaculture producer in the world. Antibiotics were extensively used to ensure the development of the intensive aquaculture; however, the use of antibiotics causes safety- and environment-associated problems. As an alternative strategy to antibiotics, aquatic probiotics have attracted attention. The microbial organisms used as probiotics or tested as potential probiotics in Chinese aquaculture belong to various taxonomic divisions, including Actinobacteria, Bacteroidetes, Firmicutes, Proteobacteria and yeast. Moreover, the mixture of probiotic strains and synbiotics are also widely used. Studies on the mode of action of aquatic probiotics have extended our understanding of the probiotic effects, and novel mechanisms have been discovered, such as interference of quorum sensing. However, use of probiotics in Chinese aquaculture is still at an initial stage, and there are potential risks for some probiotic applications in aquaculture. Further regulation and management are required to normalize the production and usage of aquatic probiotics. In this review, we discuss species, effects, and mode of actions of probiotics in Chinese aquaculture since 2008. Challenges and future directions for research are also discussed.